Invasion by exotic tree species in forest remnants in "Planalto Sul Catarinense" region Invasão por espécies arbóreas exóticas em remanescentes florestais no Planalto Sul Catarinense - Guidini A.L.* (2014)
This study evaluated the invasion by exotic tree species in two Mixed Ombrophilous Forest (FOM) fragments (F1 and F2) in Lages, SC. A total of 25 plots were allocated in each fragment, distributed in five transects, 20x100 m, perpendicular to the edges and, at least, 100 m apart from each other, where the adult (dbh - diameter at breast height ≥ 5 cm) and the regenerative (dbh < 5 cm and height ≥ 10 cm) component individuals were evaluated. These were identified and measured (circumference and height). For each component and fragment, the biological invasion index (BII) was determined. The relation between BII and the distance from the edge was evaluated by simple linear regressions. The grouping among exotic and native species was analyzed through Spearman correlation and clusters. A total of 3, 701 individuals distributed in 105 species were sampled, being five invasive species. In F1 a relative low value of BII (0.05 and 0.54) occurred, with Pinus taeda L. as the most expressive species in the invasion, and it was grouped with native pioneers species. The BII's in F2 were elevated (0.61 and 1.96), mainly due to the expressive participation of Ligustrum lucidum W.T. Aiton., grouped with typical species of FOM. No relation between the distance from the edges and the intensity of the invasion were observed. The results demonstrated that the fragments showed different biological invasion patterns that were determined by the nature of surrounding matrix and the ecological characteristics of the invasive species.